Pengaruh Dosis Pupuk Kandang Ayam Terhadap Pertumbuhan Dan Hasil Ubi Jalar (Ipomea batatas L) Varietas Cilembu - Aksameri Dolmo; Imaculata Fatima; Yustina Maria Silvia Wonga Puu (AGRICA, 2011)
The study aims at determining, firstly, the effect of chicken manure dose on the growth and crop result of sweet potato (Ipoma batatas), Cilembu Variety, secondly, determining the optimum dose of chicken manure which can lead the best of growth and yield of sweet potato (Cilembu variety). The method used at this research is completely randomized design, and the treatments are K0 (non-fertilizer), K1 (dose of 10 tons/ha), K2 (dose of 20 tons/ha), K3 (dose of 30 tons/ha). Observation variables in this study are the length of the rod, number of leaves, leaf area, number of wet bulb per plant, berangkasan weight, wet weight of bulb per plant, length of the bulb, the diameter of the bulb, and weight of wet bulb per hectare. The result of this research indicates that the giving of chicken manure, giving a good influence at the growth and yield of Cilembu sweet potato and real affect long stem at the age of 2, 6, and 8 mst of age, and wide leaf index at age 2, 4, and 6 mst. Production components have significantly affected for berangkasan weight, wet weight of bulb per plant, length of the bulb, the diameter of bulb and weight of wet bulb per hectare. The optimum dose of chicken manure was obtained with a dose of 20 tons per hectare which can raise the growth of stem length of Cilembu Sweet Potato (80,85 cm) and the crop of Cilembu sweet potato (731, 72 kg/ha).